P.127 Management and outcome of spontaneous sub-aponeurotic fluid collections in infants: the Hospital for Sick Children experience and review of literature. (17th June 2016) - Wang, S; Kulkarni, AV; Drake, J
Abstract : Background: Spontaneous sub-aponeurotic fluid collection (SSFC) is an uncommon and newly described entity of unknown etiology, observed in infants less than one year of age. In this paper, we report a series of 9 infants who presented to the Hospital for Sick Children with SSFC over the 2004 to 2015 period, focusing on the natural history of this rare condition.Methods: Data from the HSC was retrospectively reviewed. Patient age and gender, birth history, past medical history, laboratory findings, imaging characteristics, management, and outcome were analyzed.Results : Our case series consists of 4 males and 5 females, ranging from 5 weeks to 11 months of age. All cases of SSFC developed spontaneously over a period of days, and the infants had no history of injuries or hair manipulation. Six patients had a remote history of forceps or vacuum-assisted births. One patient experienced fluctuating fluid collection size over 4 months, but in all the cases, the collections resolved spontaneously without structural or infectious complications.Conclusions: This is the largest series describing SSFC to date, and summarizes the experience of a large academic neurosurgical center. SSFCs develop spontaneously without immediate preceding trauma, and an extensive hematology or child abuse workup is not necessary. A conservative approach with outpatient follow-up is advocated.